Customised multiphasic nucleus/annulus scaffold for intervertebral disc repair/regeneration. (3rd March 2020) - Gloria, A.; Russo, T.; D'Amora, U.; Santin, M.; De Santis, R.; Ambrosio, L.
ABSTRACT: Background : In the case of a degenerated intervertebral disc (IVD), even though spinal fusion has provided good short-term clinical results, an alteration of the spine stability has been demonstrated by long-term studies. In this context, different designs of IVD prostheses have been proposed as alternative to spinal fusion. However, over the past few years, much of the recent research has been devoted to IVD tissue engineering, even if several limitations related to the complex structure of IVD are still presented.Purpose/Aim : Accordingly, the aim of the current paper was to develop a strategy in designing customised multiphasic nucleus/annulus scaffolds for IVD tissue engineering, benefiting from the great potential of reverse engineering, additive manufacturing and gels technology.Materials and Methods : The device consisted of a customised additive-manufactured poly(ε-caprolactone) scaffold with tailored architectural features as annulus and a cell-laden collagen-low molecular weight hyaluronic acid-based material as nucleus with specific rheological and functional properties. To this aim, injectability and viscoelastic properties of the hydrogel were analyzed. Furthermore, a mechanical and biological characterization of cell-laden multiphasic nucleus/annulus scaffold was performed.Results and Conclusions : Analyses on the developed devices demonstrated appropriate viscoelastic and mechanical properties. As evidenced by rheological tests, the hydrogel showed a shear-thinning behaviour, supporting the possibility to inject the material. The mechanical characterization highlighted a compressive modulus which falls in the range of lumbar discs, with the typical initial J-shaped stress–strain curve of natural IVDs. Furthermore, preliminary biological tests showed that human mesenchymal stem cells were viable over the culture period.